Effect of composition and processing conditions on the chemical and morphological evolution of PA-6/EPM/EPM-g-MA blends in a corotating twin-screw extruder - Machado, A. V. (2001)
This study investigated the effect of blend composition and processing conditions on the chemical conversion and morphological evolution of PA-6/EPM/EPM-g-MA blends along a twin-screw extruder. The maleic anhydride (MA) content of the modified rubber was found to decrease strongly, to a level of almost zero, and in the melting zone the particle size was dramatically reduced, from millimeters to submicrometers. Blend composition had a secondary effect on both chemical conversion and morphological development. The processing conditions, particularly the temperature profile and the screw speed, affected both the chemical conversion and the morphological Evolution. Using low temperatures and low screw rotation it was possible to follow in detail the evolution of morphological development of a reactive blend in a twin-screw extruder.